Demographic profile of children with nephrotic syndrome in Hospital Universiti Sains Malaysia - Nik Mat, Shuib (2007)
Steroid is still the mainstay therapy for nephrotic syndrome and up to 70% of children had frequent relapses or steroid dependent. But some of the cases are resistant to steroid therapy. Immunosuppressive drugs, such as cyclosporine A, cyclophosphamide, chlorambucil and levamisole have proved effective as steroid-sparing agents. Cyclosporine was frrst started in our hospital HUSM (Hospital Universiti Sains Malaysia) in 1996 for steroid resistant NS (nephrotic syndrome) following renal biopsy. There were no published data from locally regarding the demographic profile of the children with nephrotic syndrome, the outcome, side effect and prognosis toward development of renal failure in children with NS treated with cyclosporine. Objectives: To describe the demographic data of children with nephrotic syndrome treated in HUSM. To determine common side effect that are related to the use of cyclosporine and development of renal failure in children with nephrotic syndrome treated with cyclosporine. Methodology: This is a retrospective study in which all children with NS below 15 years old were reviewed. All the results were analyzed using Statistical Package for the Social Sciences Programmed (SPSS) for Window version 12.0. For each case, demographic data, renal biopsy results, respond and side effect were presented by percentage, median and interquarter range. Friedman test were used to assess differences between repeated continuous variables. Statistical significance was inferred at p <0.05. Result: There were 83 children's with nephrotic syndrome on treatment and follow up at HUSM. These figures give about 0.48% of the total admission of paediatric medical cases to HUSM during study period. The mean age at presentation was 6.39 (±SD3.41) years Children with steroid sensitive nephrotic syndrome occurred in 85.5% (n=71) compare to children with steroid resistant nephrotic syndrome occurred in 14.5% (n=12). Relapse occurred in 63.9% of all NS children (n=53) and 36.1 % of children (n=30) had no relapse. There were 57.7% of children (n=41) with SSNS (steroid sensitive nephrotic syndrome) experience relapse and 42.3% of these group of children (n=30) had no relapse. Cyclosporine has been used in 21.6% [95%CI (12.6%, 30.7%)] ofNS children (n=18) and 66.7% (n=12) of the children were due to steroid resistant and 33.3% (n=6) of the children were due to steroid toxicity. Side effects noted in this study were gum hypertrophy 55.6% (n=10), hirsutism 16.7% (n=3) and renal impairment 16.7% (n=3). There were 27.8% (n=5) of these children, free of any side effects. There were 14 out of 18 children had hypertension before cyclosporine and 12 of them still noted to have hypertension after cyclosporine, 2 children loss follow up and 4 children had no hypertension before or after cyclosporine. There were 56.0% children with normal renal function in steroid resistant nephrotic syndrome and 60.0% children with normal renal function in steroid toxicity NS at the end of the study over the period of 5 years (60 months). Conclusion: Majority of the children with nephrotic syndrome treated in Hospital Universiti Sains Malaysia were steroid sensitive. Cyclosporine had been used in case of steroid resistant nephrotic syndrome and steroid toxicity nephrotic syndrome. Findings from our study found that cyclosporine is a safe drug and could be considered in the treatment of children with steroid resistant or steroid toxicity nephrotic syndrome.